An animal model in rat for secondary osteoporosis: the effect of gonadotropin-releasing hormone (GnRH) agonists, low calcium diet, and immobilization on tartrate-resistant acid phosphatase 5b (TRACP-5b) and procollagen type 1 N-terminal propeptide (PINP) levels - Panji Sananta; Respati Suryanto Dradjat; Istan Irmansyah Irsan; Andhika Yudistira; Aditya Rosid Dwi Anwar (Medicinski glasnik, 2026)
Aim: Osteoporosis is a global health concern, characterized by reduced bone density, microarchitectural changes, and an increased risk of fractures. The prevalence of osteoporosis is rising, particularly in developing countries. In Indonesia, the incidence of upper femur fractures due to osteoporosis is notably high. As human studies are limited, animal models are crucial for investigating osteoporosis, with several methods used to induce the condition. This study proposes an alternative model using leuprolide acetate, gonadotropin-releasing hormone (GnRH) agonist, combined with a low-calcium diet and immobilization, to induce secondary osteoporosis in animals. Methods: This experimental study employed a post-test-only control group design with 12 groups of Wistar rats (Rattus norvegicus). Three control groups received no treatment, while nine experimental groups were administered leuprolide acetate along with a low-calcium diet and immobilization. The study measured tartrate-resistant acid phosphatase 5b (TRACP-5b) and procollagen type 1 N-terminal propeptide (PINP) levels in rat bone tissue. Results: Significant increase in TRACP-5b and decrease in PINP levels were observed on days 21, 28, and 35 in the treated groups. Post hoc analysis revealed significant differences between treatment groups. Conclusion: The experimental model successfully demonstrated a reliable and reproducible method for inducing secondary osteoporosis. Elevated TRACP-5b and reduced PINP levels indicate increased osteoclast activity and decreased osteoblast activity resulting from excessive bone remodelling. The combination of leuprolide acetate, a low-calcium diet, and immobilization is an effective and alternative method for inducing secondary osteoporosis in experimental animals.
Keywords: calcium; immobilization; leuprolide; osteoporosis